2019
DOI: 10.1038/s41594-019-0310-2
|View full text |Cite
|
Sign up to set email alerts
|

Naa10P puts a brake on PGC1α and fat browning

Abstract: Beige fat serves as a substantial metabolic sink that dissipates energy and has consequently attracted much attention as a target for improving metabolic health. A recent study has provided a new molecular target, the N-terminal acetyltransferase Naa10p, for harnessing beige-fat biogenesis and improving whole-body energy homeostasis1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…A recent study showed that N-α-acetyltransferase 10 protein (NAA10) catalyzes the N-terminal acetylation of PGC1α and inhibits PGC1α activity by preventing its recruitment to the Ucp1 promoter [20]. However it is not yet known whether N-α-acetylation of PGC1α is reversible and how it is regulated [21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that N-α-acetyltransferase 10 protein (NAA10) catalyzes the N-terminal acetylation of PGC1α and inhibits PGC1α activity by preventing its recruitment to the Ucp1 promoter [20]. However it is not yet known whether N-α-acetylation of PGC1α is reversible and how it is regulated [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, brown adipocytes are characterized by their high mitochondrial content and expression of uncoupling protein 1 (UCP1) (17,18). Lastly, beige adipocytes are located within subcutaneous WAT depots, and are derived from precursor cells upon environmental cues such as cold exposure, through a process known as "browning" (16,19,20). Interestingly, although beige adipocytes have a lower basal expression of UCP1 relative to brown adipocytes, it has been demonstrated that their thermogenic capacity can be raised to levels comparable to that of brown adipocytes upon stimulation (19).…”
Section: Introductionmentioning
confidence: 99%